Strategi Wakil Kepala Kesiswaan dalam Menangani Kenakalan Remaja di Era Digital: The Deputy Head of Student Affairs' Strategy in Handling Juvenile Delinquency in the Digital Age - Fiftiyansyah, Mohamad Dzikri; Ali, Mohamad (Institut Agama Islam Daruttaqwa Gresik, 2024)
This study aims to analyze the strategies the Vice Principal of Student Affairs (Waka Kesiswaan) implemented in addressing juvenile delinquency in the digital era at SMP Muhammadiyah 2 Masaran. Juvenile delinquency in the digital era includes cyberbullying, fighting, and addiction to social media and online games. This study uses a qualitative approach with a case study method involving participant observation, semi-structured interviews, and document studies. The results of the survey show that juvenile delinquency is influenced by internal factors, such as lack of self-control, as well as external factors, such as environmental influences and lack of parental supervision. The Vice Principal of Student Affairs applies three main strategies: preventive, repressive, and curative. Preventive measures include instilling religious values, implementing school rules, and providing counseling services. Repressive actions involve giving advice, punishment, and coordinating with parents. Meanwhile, curative actions involve training, discipline, and collaboration with various parties. This study recommends that schools improve the effectiveness of handling juvenile delinquency through a holistic and collaborative approach. Implications: This study's implications emphasize the importance of a comprehensive approach to addressing juvenile delinquency. Collaboration between schools, parents, and the community is crucial to creating an environment that supports adolescents' development. Adapting strategies to technological advancements and social media is essential. Schools are expected to continuously develop programs that strengthen students' character and social skills to handle juvenile delinquency effectively and sustainably.